Modelling the thermal inactivation of five Campylobacteraceae species. (January 2015) - Scanlon, Karl A.; Tiwari, Uma; Cagney, Claire; Walsh, Des; McDowell, David A.; Duffy, Geraldine
Abstract: This study investigated the thermal inactivation of five Campylobacteraceae species ( Campylobacter coli, Campylobacter helveticus, Campylobacter concisus, Campylobacter fetus subsp. fetus and Arcobacter butzleri ) at 55 and 60 °C using an immersed coil heating apparatus. The applicability of nine different models, including log linear and Weibull type models, some of which accounted for shoulders and tailing populations at the start or end of the heat treatment, was assessed to describe the thermal inactivation of each species. The Weibull model with tailing effect provided a good fit with low RMSE value (0.07–0.27), AICc (−88.12 to −6.82) and high R 2 values (0.97–0.99) depending on the temperature and the species. The Weibull + tail model showed a significantly high D value for Arcobacter butzerli (180.2 s) at 55 °C and a low D value for C. helveticus (23.9 s) at 60 °C, with a high degree of variability in thermal tolerance noted across the species. Moreover, the Weibull + tail model also indicated high thermal sensitivity for C. fetus subsp. fetus at both temperatures investigated. This study highlights the value of assessing various inactivation models to describe the D value to get the model which best describes the survival data. These model predictions enhance knowledge about the survival characteristics and behaviour of fastidious Campylobacteraceae in the food chain. Highlights: Thermal inactivation of 5 Campylobacteraceae species was examined at 55 and 60 °C. Nine models were compared to assess the thermal behaviour for each species. The Weibull model with tailing effect was identified as the best model. There was considerable variation in thermal tolerance across the five species. Campylobacter fetus subsp. fetus was the most thermosensitive at 55 and 60 °C.